2020
DOI: 10.1111/ddi.13183
|View full text |Cite
|
Sign up to set email alerts
|

A blueprint for securing Brazil's marine biodiversity and supporting the achievement of global conservation goals

Abstract: Aim: As a step towards providing support for an ecological approach to strengthening marine protected areas (MPAs) and meeting international commitments, this study combines cumulative impact assessment and conservation planning approach to undertake a large-scale spatial prioritization. Location: Exclusive Economic Zone (EEZ) of Brazil, Southwest Atlantic Ocean. Methods: We developed a prioritization approach to protecting different habitat types, threatened species ranges and ecological connectivity, while a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
39
0
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(45 citation statements)
references
References 88 publications
0
39
0
4
Order By: Relevance
“…In Brazil, effectiveness of MPAs in terms of increase in the abundance and biomass of fish inside its boundaries has been relatively well documented Halpern & Ferreira, 2006;Prates et al, 2007;Anderson et al, 2014), but reports on benefits through spillover to adjacent areas and effectiveness in terms of biodiversity protection and fisheries benefits are scarce. Also, connectivity of Brazilian MPAs through larval dispersion has been discussed (Endo et al, 2019), as well as its implication on the design of a representative MPA system (Magris et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…In Brazil, effectiveness of MPAs in terms of increase in the abundance and biomass of fish inside its boundaries has been relatively well documented Halpern & Ferreira, 2006;Prates et al, 2007;Anderson et al, 2014), but reports on benefits through spillover to adjacent areas and effectiveness in terms of biodiversity protection and fisheries benefits are scarce. Also, connectivity of Brazilian MPAs through larval dispersion has been discussed (Endo et al, 2019), as well as its implication on the design of a representative MPA system (Magris et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…A recent study by Magris et al (2021) in Brazil revealed priority areas for marine conservation (Figure 1). The authors reveal that industrial fishing, climate change and terrestrial activities, linked to the production of waste, were the greatest threats to biodiversity, and stress the importance of a comprehensive ecological approach when identifying strategic conservation priorities.…”
Section: The Brazilian Coast and The Impacts Of National Unsustainabilitymentioning
confidence: 98%
“…These islands have among the highest fish biomass across Brazilian reefs (Morais et al, 2017), notable endemism (Simon et al, 2013;Pinheiro et al, 2020), and globally threatened fauna (Almeida et al, 2011;Duarte-Neto et al, 2012). Despite their biodiversity significance, both regions are also threatened by commercial fisheries and climate change (Magris et al, 2020). The MPAs comprise the territorial sea and exclusive economic zones of the islands.…”
Section: Case Study Descriptionmentioning
confidence: 99%
“…For this last set of analyses, I compared each measure of fishing pressure calculated as above against the same metrics associated with cells randomly selected across Brazil's EEZ, and limited to the corresponding total size of one set of large-scale MPAs (i.e., 455,000 km 2 ). I generated the random selection of cells as described in Magris et al (2020). I restricted the cells selection within other areas of Brazil's EEZ because international waters can have different fisheries management regulations.…”
Section: Commercial Fishing Activitymentioning
confidence: 99%
See 1 more Smart Citation